UPAYA PEMERINTAH KOTA PEKANBARU MENINGKATKAN DAYA SAING USAHA KECIL MENENGAH DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN TAHUN 2016 - Muhammad Firdaus; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research describes the effort of government of Pekanbaru toward the competitions of micro and small bussiness in Asean Economic Community in 2016. Asean Economic Community are one of modells economic integrations to create a common market in Southeast Asia regions. Micro and small business are one of micro economic modells in Indonesia that have big potency for economic growth in Indonesia.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the effort of government of Pekanbaru toward the competitions of micro and small bussiness in Asean Economic Community. The theories applied in this research are neoliberalism perspective with the globalization theory by Robert W Cox.The research shows that the effort of government of Pekanbaru toward the competitions of micro and small bussiness in Asean Economic Community are by controlling and supervised. Some steps are have done by government of Pekanbaru are doing socializations of Asean Economic Community, give a supervised, held a consultations bussiness and controlling by create a bureaucrations for investations in Pekanabru city.Key words: asean, economic community, invest and micro small business